Linking Mobile Communications with the United Nations Sustainable Development Goals: Mapping Process - Kirsi Ojutkangas; Elina Rossi; Sirpa Aalto; Marja Matinmikko-Blue (International Telecommunications Society (ITS), 2020)
United Nations Sustainable Development Goals (SDGs) are becoming an increasingly important theme for researchers in multiple fields to investigate. In this paper we look at the process of how 6G researchers and other experts identified ways in which mobile communications is linked with the UN SDGs while writing a new 6G white paper on the topic. In a team of around 40 members consisting of representatives of academia, industry, and governmental bodies, we developed a sustainable vision for 6G, identified linkages between 6G mobile communications and the UN SDGs, and came up with a preliminary plan of action for how to reach the set goals, all published in a white paper. It is to be noted that the technological development for 6G is very much in its infancy, thus we concentrated our work on mobile communications in general and looked at the possible linkages between 6G and the UN SDG's from the perspective of what could be and what should be. In this paper we look into the detailed operations of the expert group and describe the mapping process for finding the linkage between the UN SDGs and 6G in a way that may guide other researchers in related endeavours. The aim of this paper is threefold: 1) to briefly present the relevant linkages between the UN SDGs and mobile communications, 2) to look at the process of identifying the relevant UN SDGs for mobile communications research from a theoretical perspective, and 3) to formulate a working mapping process to be widely adopted. We will describe the background, i.e. the findings of the white paper expert group, and then move on to describing the process itself, and finally present a mapping process to be adopted.
Keywords: 330